Understanding philosophy of science - Ladyman, James, 1969- (London ; New York : Routledge, 2002)
"Without scientific theory, the technology developments of recent years would not have been possible. In this introduction to philosophy of science, James Ladyman explores the scope of natural science and its implications for human life. With the focus firmly upon realism, he discusses how fundamental philosophical questions can be answered by science and how scientific theory can confirm and inform our basic and intrinsic knowledge."--BOOK JACKET.
I. The Scientific Method -- 1. Induction and Inductivism -- 2. The Problem of Induction and other Problems with Inductivism -- 3. Falsificationism -- 4. Revolutions and Rationality -- II. Realism and Antirealism about Science -- 5. Scientific Realism -- 6. Underdetermination -- 7. Explanation and Inference to the Best Explanation -- 8. Realism about What?
Includes bibliographical references (p. 270-275) and index.
Keywords: Science -- Philosophy